identification of a bacteriocin producing by Lactococcus lactis subsp. Lactis PD14 - Thi Minh Tu, Hoa; La Anh, Nguyen; Thanh Binh, Le (Vietnam Journal of Science and Technology, 2017)
The strain Lactococcus PD14 isolated from cow’s fresh milk was identified as Lactococcus lactis subsp. lactis. The bacteriocin produced by PD14 was isolated and purified by absorption-desorption method described and then this bacteriocin was purified by solid-phase extraction-SPE and HPLC method with column C18. The result of tricine- SDS-PAGE indicated the molecular weight of bacteriocin was about 3.5 kDa, the same as nisin. The prenisin encoding gene was cloned and sequenced successfully for PD14. The nis gene of the strain PD14 was 99 % homology with nisA and nisZ while 98 % with nisF, 97 % with nisQ. The deduced amino acid sequence of prenisin was determined, which had minor difference from published sequence of nisA in one amino acid. At the position aminoacid -18, prenisin of PD14 had valine while the known prenisin A had phenylalanine. The matured nisin of PD14 was completely similar to the known amino acid sequence of nisA. Thus, the strain Lactococcus lactis subsp. lactis. PD14 produced a bacteriocin which was identified as nisin A.